Soliloquy Language in Badr Shaker Al- Sayyab's Poem Stranger on the Bay - Amer Hashem Mohamed, Lect. Dr. (lark, 2022)
Stranger on the Bay is one of the most famous poems; its language is intense, uniting a variety of modes or rhetorical languages, for example, the language of grief, the language of nostalgia, the language of alienation, and so on. If we read the poem carefully, we will discover that it is addressed the concept of the stranger, as one of the reasons for alienation is that it requires the stranger to connect with the unseen in the absence of one. Thus, we witness him communicating with his soul in a variety of languages, most notably the supplication language. It is repeated in multiple poems as a result of his belief in the unseen and the creator who rescues him from this pain.